2010
DOI: 10.1073/pnas.1012104107
|View full text |Cite
|
Sign up to set email alerts
|

Correction of respiratory disorders in a mouse model of Rett syndrome

Abstract: Rett syndrome (RTT) is an autism spectrum disorder caused by mutations in the X-linked gene that encodes the transcription factor methyl-CpG-binding protein 2 (MeCP2). A major debilitating phenotype in affected females is frequent apneas, and heterozygous Mecp2-deficient female mice mimic the human respiratory disorder. GABA defects have been demonstrated in the brainstem of Mecp2-deficient mice. Here, using an intact respiratory network, we show that apnea in RTT mice is characterized by excessive excitatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 39 publications
14
159
2
3
Order By: Relevance
“…In LC neurons, our previous studies have shown that the postsynaptic GABA A and GABA B currents are both defective in Mecp2-null mice (10). Consistent with these findings, the therapeutic GABA A R activators diazepines and the reuptake blocker NO-711 improve RTT symptoms in animal models, including breathing (20,21). However, it is still unclear how the extrasynaptic GABA A Rs are affected in Mecp2-null mice, which makes this study remarkable.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In LC neurons, our previous studies have shown that the postsynaptic GABA A and GABA B currents are both defective in Mecp2-null mice (10). Consistent with these findings, the therapeutic GABA A R activators diazepines and the reuptake blocker NO-711 improve RTT symptoms in animal models, including breathing (20,21). However, it is still unclear how the extrasynaptic GABA A Rs are affected in Mecp2-null mice, which makes this study remarkable.…”
Section: Discussionsupporting
confidence: 61%
“…(4, 13, 20, 33, 56 -58), which is likely to be due to impaired synaptic transmission and intrinsic membrane properties. The highly excitable state of some of these neurons seems to contribute to cognitive defects, motor abnormality, and breathing disturbances (9,20,56,57). Clearly, such an overexcitation in central neurons can be alleviated by GABAergic inhibition, in which excessive extrasynaptic GABA A Rs are beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Drd5 (encoding for a dopamine receptor) and Tdo2 (encoding for the rate-limiting enzyme in the synthesis of serotonin tryptophan 2,3-dioxygenase) play a role in serotonin signalling and have been related to attention deficit-hyperactivity disorder and autism spectrum disorder [37][38][39][40] . The case of Rett syndrome (RS) is particularly interesting because (i) this congenital disorder associated with intellectual disability and autism has been recently related to impaired heterochromatin clustering 15 and chromocenter alterations during neuronal maturation 16 ; (ii) RS is caused by mutations in the gene encoding methyl CpG binding protein 2, one of the proteins showing abnormal distribution in H2BGFP-expressing neurons; (iii) the dysfunction of monoaminergic systems is known to be an important component of RS neuropathology 41 and 5-HT1A agonists, such as the one used in our study, prolong the life of mouse model of the disease 42 and are useful in the treatment of respiratory dysfunction in RS patients 43 ; and (iv) recent transcriptomics analyses show that Htr1a and Htr2a are downregulated in the hippocampus of mouse models of RS 44 . The transcriptional and behavioural deficits in H2BGFP mice also relate to negative symptoms in schizophrenia, such as prepulse inhibition and cognitive impairments, and reduce motivational drive.…”
Section: Discussionmentioning
confidence: 99%